2021
DOI: 10.1101/2021.03.26.21254398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Randomized Trial - Intensive Treatment Based in Ivermectin and Iota-Carrageenan as Pre-Exposure Prophylaxis for Covid- 19 in Healthcare Agents

Abstract: IMPORTANCE: The emergency of COVID-19 requires the implementation of urgent strategies to prevent the spread of the disease, mainly in health personnel, who are the most exposed and has the highest risk of becoming infected with the SARS-COV-2. Drug repurposing is a pragmatic strategy, a faster and cheaper option, compared to the new drug development that has proven successful for many drugs and can be a key tool in emergency situations such as the current one that requires quick action. In addition, consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 30 publications
(37 reference statements)
1
43
0
Order By: Relevance
“…Supporting the findings of IVM efficacy in COVID-19 treatment as summarized above were indications of activity against SARS-CoV-2 in prevention studies. Three RCTs evaluated the prophylactic effect of IVM administered to cohorts of 100 [ 22 ], 117 [ 39 ] and 203 [ 40 ] subjects exposed to COVID-19 patients. These studies, all using IVM in doses of at least 150 μg/kg per week, reported statistically significant reductions in COVID-19 incidences, with respective RRs of 20%, 26% and 13% as compared with controls, and greater reductions in incidences of moderate and severe cases.…”
Section: Rcts For Ivm Treatment and Prevention Of Covid-19mentioning
confidence: 99%
“…Supporting the findings of IVM efficacy in COVID-19 treatment as summarized above were indications of activity against SARS-CoV-2 in prevention studies. Three RCTs evaluated the prophylactic effect of IVM administered to cohorts of 100 [ 22 ], 117 [ 39 ] and 203 [ 40 ] subjects exposed to COVID-19 patients. These studies, all using IVM in doses of at least 150 μg/kg per week, reported statistically significant reductions in COVID-19 incidences, with respective RRs of 20%, 26% and 13% as compared with controls, and greater reductions in incidences of moderate and severe cases.…”
Section: Rcts For Ivm Treatment and Prevention Of Covid-19mentioning
confidence: 99%
“… 94 The treated group also had a lower prevalence of mild to moderate COVID-19 presentation compared to the control group. 94 This intensive preventive treatment with iota-carrageenan and ivermectin was able to significantly reduce the number of infected health care workers. 94 The study using iota-carrageenan in a single dose is still ongoing under the register numbers NCT04793984, NCT04681001, and NCT04590365.…”
Section: Resultsmentioning
confidence: 86%
“… 93 In 2021, a randomized controlled 1-1 clinical trial under registration NCT04701710 was conducted to prioritize health personnel infected with SARS-CoV-2 (n = 232) at Argentina's Public Healthcare Centre, using the same iota-carrageenan and ivermectin regimen as in the previous study. 94 The result indicated that the number of subjects diagnosed with COVID-19 was significantly lower in the treated group, at 3.4%, than in the control group, at 21.4% (p = 0.0001). 94 The treated group also had a lower prevalence of mild to moderate COVID-19 presentation compared to the control group.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations